Strategic Framework for the Organization of Regional Head Elections (Pilkada) by the General Election Commission (KPU) in Southern Sumatra (Lampung, Jambi, Bengkulu, and Babel) during the COVID-19 Pandemic - Redi Pirmansyah; Junaidi; Martindo Merta (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Indonesia’s democratization, particularly through regionalhead elections (Pilkada), has been a significant step indecentralization and empowering citizens. However, theCOVID-19 pandemic introduced unforeseen challenges inexecuting these elections. The pandemic created a tensionbetween maintaining democratic participation andaddressing public health concerns, making it difficult fortraditional election campaigns and procedures to continueas usual. This study explores how the General ElectionCommission (KPU) of Indonesia adapted the regional headelections in Southern Sumatra in response to the COVID19 pandemic. Specifically, it aims to evaluate the strategicadjustments made by the KPU to balance democraticprocedures with health protocols during the crisis. Theresearch utilizes a qualitative descriptive approach,focusing on document analysis of relevant regulations suchas Government Regulation No. 2/2020 and KPURegulations No. 5 and 6/2020. The study assesses themodifications made to electoral procedures to ensure thecontinuity of democratic processes while prioritizing publichealth. The findings demonstrate that the KPUsuccessfully implemented several strategies to ensure thesafety of voters and election participants during thepandemic. These strategies included strict health protocols,virtual communication methods, and educationalcampaigns aimed at increasing voter awareness. Despitethe challenges, the KPU managed to facilitate elections thatadhered to health guidelines while promoting active civicparticipation.